THE ROLE OF PANCASILA IN RAISING GENERATION Z’s RELIGIOUS AWARENESS - Muhammad Harkim Novridho; Rizal Al Hamid (Jurnal Humaniora & Sosial Sains, 2024)
The article discusses the role played by Pancasila in enhancing the religious awareness of Generation Z in Indonesia. The aim of this research is to comprehend the function of Pancasila as a framework to address the challenges related to religion faced by Generation Z. This study is conducted in response to the necessity of maintaining harmony between religion and ideology in a society living amidst religious diversity. The research method utilized is a literature review involving the collection and analysis of various literature pertaining to this topic. The findings of this research identify five main dimensions in the role of Pancasila, namely the Oneness of God in religious diversity, humanity that is just and cultured in combating radicalism, the unity of Indonesia in upholding the commitment of the nation among the religious community, democracy led by the wisdom of deliberation/representation in maintaining the values of the religious community's democracy, and social justice for all Indonesians in preserving the accommodative values towards local wisdom.